Mathematical theories for two classes of thermoelastic contact problems. (15th October 2022) - Howell, Peter; Ockendon, John; Shillor, Meir
Abstract: This paper reviews some of the mathematical research that has been inspired by Jim Barber's pioneering experimental and theoretical work on thermoelastic contact problems. The first part considers rod-contact problems in the absence of wear, but allowing for elastic waves, and the second part focuses on the effect of wear over time-scales when elastic waves are negligible.